ANALISIS MEKANISME TRANSMISI KEBIJAKAN MONETER DI INDONESIA: PEMODELAN MUNDELL-FLEMING - Tongku Ahmad Husen Daulay (Departemen Ekonomi Pembangunan USU, 2013)
This research intentsfor analyzing how monetary policy transmission mechanism that has been happened Indonesia through Mundell-Fleming's modelling within 2000:1 - 2012:4. Variable that was utilized for this research consist of money supply, interest rate, exchange rate, net export and gross domestic product. Equation system was utilized in this research is VAR. Previously it has been done stasionerity test, granger’s causality test and cointegration test to data that wasused. Then continuedby Impulse Response Function and Variance Decomposition. The result of research showed that during transmission mechanism research period of monetary policy in Indonesia with Mundell Fleming's modelling mutually give contribution to another variable, either short in the termor longterm.Keywords: Monetary policy transmission mechanism, Mundell Fleming, VAR, Stasionerity, Causality of Granger, Cointegration.